Creative power and productive domestication in piaroa and kaxinawá aesthetics - Lagrou, Elsie Maria (Cadernos de Campo (São Paulo, 1991), 1996)
In this article, the esthetical concepts of Piaroa and Kaxinawá and the role they play in their societies are compared. “Art” and esthetic, because they interact with other symbolic systems (the music, the ritual and the social organization), allow us to understand the way power, knowledge and the kinship are conceived in those societies.